Fretibacterium sp. human oral taxon 360 is a novel biomarker for periodontitis screening in the Japanese population - Khemwong, Thatawee (PLoS One, 2019)
BACKGROUND: Periodontitis is a common inflammatory disease, leading to bone destruction and tooth loss. Screening for periodontitis is important in preventing the progress of this disease. Various types of bacteria have been examined as potential screening targets, but only culturable pathogenic bacteria have been considered candidates. Recently, the various uncultivable bacteria have been identified in microbiome studies, but the value of these bacteria in periodontitis screening remains unknown. OBJECTIVES: The aim of this study was to evaluate the diagnostic use of uncultivable bacteria Fretibacterium sp. HOT 360 and TM7 sp. HOT 356 for periodontitis screening in the Japanese population. MATERIAL AND METHODS: Stimulated saliva samples were collected from 217 participants (periodontitis group, n = 157; healthy group, n = 60). The two uncultivable bacterial species selected were: Fretibacterium sp. human oral taxon 360 (Fretibacterium sp. HOT 360) and TM7 sp. human oral taxon 356 (TM7 sp. HOT 356). The levels of these two bacterial species were compared with those of Porphyromonas gingivalis (P. gingivalis), a keystone pathogen in periodontitis. These three species of bacteria were then quantified using qualitative real-time polymerase chain reaction (qPCR) with specific primers and Taqman probes. Statistical analysis was performed by SPSS 20.0 software. P value was statistically significant at .05. RESULTS: The populations of uncultivable bacterial species TM7 sp. HOT 356 and Fretibacterium sp. HOT 360 were significantly higher in periodontitis group than in healthy group. Only Fretibacterium sp. HOT 360 showed a significantly positive correlation with such periodontal parameters as probing pocket depth (PPD) and bleeding on probing (BOP). CONCLUSION: These findings indicate that uncultivable bacteria Fretibacterium sp. HOT 360 can be used as a saliva-based diagnostic bacterial biomarker for periodontitis screening.